Веб-технологій в управлінні проєктами: бібліографічна карта дослідження - Снігур, А. Р. (ХНУРЕ, 2024)
In this work, a bibliometric analysis of trends in web technologies in the field of project management was carried out in order to identify key problems and directions of research. The study analyzed various metrics, such as the annual number of publications and the most used keywords. The following keywords were most relevant: knowledge management, agent, teaching, world, community, information technology. The relevance of these keywords indicates that the topics of training, knowledge management, and information technologies were of great interest to the authors during the research. Thus, on the basis of the obtained results, it is possible to draw a conclusion about the potential directions of further research in this area.
Keywords: бібліографічна карта дослідження; управління проєктами